1983
DOI: 10.1029/jc088ic15p10667
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of monoterpene hydrocarbons at Niwot Ridge, Colorado

Abstract: Measurements of atmospheric monoterpene hydrocarbons were made at a site in the Colorado mountains. The research was undertaken to examine the influence of the compounds on the photochemistry of the troposphere. A sampling technique was developed using Tenax GC porous polymer traps with analysis by capillary gas chromatography and detection by flame ionization and mass spectrometry. Positive identification of six monoterpene hydrocarbons, •-pinene, camphene, ]•-pinene, myrcene, A-3carene, and d-limonene, was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

1983
1983
1990
1990

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…The lower ozone concentration below this inversion is presumably due to surface destruction. Alternatively, titration of 03 by NO or naturally occurring unsaturated hydrocarbons, which are emitted by vegetation, cannot be important because of the low concentrations observed for these species (Roberts et al, 1983b). The degree of ozone suppression that occurs during a given night depends on a variety of factors including wind speed, cloud cover and stability of the inversion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower ozone concentration below this inversion is presumably due to surface destruction. Alternatively, titration of 03 by NO or naturally occurring unsaturated hydrocarbons, which are emitted by vegetation, cannot be important because of the low concentrations observed for these species (Roberts et al, 1983b). The degree of ozone suppression that occurs during a given night depends on a variety of factors including wind speed, cloud cover and stability of the inversion.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the observed increase in daytime ozone mixing ratio would have correlated with the concentrations of these anthropogenic compounds also. On the other hand, Roberts et al (1983b) have shown that terpenes contribute little to the observed O3 production primarily because of their low concentrations. The importance of other natural NMHC cannot be rigorously assessed since they are not measured at the site.…”
Section: Discussionmentioning
confidence: 99%
“…The use of combinations of different adsorbents in series can Increase the range of organic volatiles which might be determined by adsorptIOn-thermal desorption techniques [SS], but the problem of artefact formation increases with the number of different adsorbents used. The main problem which limits the applicability of adsorptive sampling is the formation of artefacts and losses by various mechanisms [41,[56][57][58][59][60][61][62][63][64][65][66]. Apart from the formation of artefacts during sample desorption by thermal decay of the sorbent, the main source of sample degradation are the reaction of reactive adsorbed compounds with each other, eIther during sampling or during storage, the reactIOn of adsorbed organic compounds with reactive trace species in the gas phase, e.g., ozone or nitrogen dioxide, and the thermal decay of sampled compounds during desorption.…”
Section: Thermal Desorptlonmentioning
confidence: 99%
“…Losses primarily occur for compounds which are easily oxidized, e.g., by ozone, such as dienes. These losses can be reduced by minimizing the sample volume and the sampling time [41]. Artefacts are primarily oxygenated hydrocarbons (aldehydes, ketones, etc.…”
Section: Thermal Desorptlonmentioning
confidence: 99%
See 1 more Smart Citation